Integrasi Teknologi Digital dalam Pembelajaran Pendidikan Agama Islam (PAI) di Era Digital - Burhanudin Khairi; Agus Pahrudin; Nanang Supriadi; Ali Murtadho (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
Digital technology has reshaped educational practice and requires Islamic Religious Education (PAI) to adopt learning designs that are pedagogically effective while remaining grounded in Islamic values. This library research aims to analyze the forms of digital technology integration in PAI learning, its pedagogical benefits, and the challenges that emerge in implementation. Data were collected through documentation of relevant books, scientific journal articles, proceedings, official documents, and electronic sources, then analyzed using qualitative descriptive analysis through identification, classification, comparison, and synthesis of the literature. The findings indicate that learning applications, interactive videos, e-learning platforms, social media, digital Qur’an applications, and artificial intelligence can support more flexible, interactive, and student-centered PAI learning. These technologies improve learning motivation, conceptual understanding, creativity, digital literacy, and teacher efficiency. Nevertheless, implementation remains constrained by unequal infrastructure, limited teacher digital competence, weak parental supervision, and the risk of exposure to inappropriate digital content that may affect students’ morals and social interaction. Therefore, the integration of digital technology in PAI should be accompanied by teacher professional development, adequate facilities, ethical digital literacy, parental involvement, and blended learning models. The study implies that digital innovation in PAI must be positioned not merely as media modernization but as a value-based pedagogical strategy that strengthens Islamic character in the digital era.